Penatalaksanaan Fisioterapi Pada Kasus Bell’s Palsy Sinistra et Causa Diabetes Melitus Dengan Kombinasi Modalitas Electrical Stimulation Facialis dan Mirror Exercise - Oktaviani Fitriyah; Ajeng Sabtorini; Salma Hira Ayu Setyara; Rizka Salsabila Putri; Kurnia Lutfi Farizqi; Indri Setyaningsih; Isnaini Herawati (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Bell's palsy is a problem with the cranial nerve in the face idiopathically without being accompanied by other neurological diseases, this has an impact on one-sided facial paralysis. Of the 126 patients who experienced bell's palsy 39% of them had diabetes mellitus. Diabetes mellitus correlates with the presence of microangiopathy due to failure of vasa nervosum microcirculation which has the potential to worsen the condition of bell's palsy patients. The combination of electrical stimulation facialis and mirror exercise treatment is performed on bell's palsy sinistra patients to accelerate recovery. The method of obtaining information related to the patient's condition through observation, interviews, medical records and then providing appropriate treatment. The purpose of this study was to determine the effectiveness of electrical stimulation facialis and mirror exercise treatment in bell's palsy patients. The results obtained increased facial muscle strength T1, T2, T3 in bell's palsy patients. Evaluation of functional effectiveness also increased T1: 66, T2: 81, T3 : 88. This treatment is considered capable of accelerating recovery in patients with bell's palsy.